Re-Detection versus New Acquisition of High-Risk Human Papillomavirus in Mid-Adult Women - Fu, Tsung-chieh (Jane) (Int J Cancer, 2016)
To understand high-risk (hr) human papillomavirus (HPV) epidemiology in mid-adulthood, we assessed whether associations between incident detection of hrHPV DNA and recent sexual behavior differed according to whether or not there was serologic evidence of prior infection. From 2011–2012, we enrolled 409 women aged 30–50 years into a 6-month longitudinal study. We collected health and sexual behavior histories, enrollment sera for HPV antibody testing, and monthly self-collected vaginal swabs for HPV DNA genotyping. Generalized estimating equations logistic regression identified risk factors for type-specific incident hrHPV DNA, stratified by type-specific hrHPV serostatus at enrollment. Population attributable risks of hrHPV due to prior and recent exposure were estimated. When type-specific hrHPV serology was negative, recent sexual risk behavior was positively associated with incident hrHPV DNA (odds ratio in women reporting ≥3 recent sexual risk behaviors [e.g., new or multiple partners] versus no recent sexual activity=9.8, 95%CI:2.4–40.6). No associations with recent sexual behavior were observed with positive type-specific hrHPV serology. Thirty percent of incident hrHPV DNA detection was attributable to prior infection (with positive serology) and 40% was attributable to recent sexual risk behavior (with negative serology). The proportion of incident hrHPV DNA detection attributable to recent sexual risk behavior decreased with increasing age. Among women with serologic evidence of prior infection, re-detection of the same hrHPV type is likely due to reactivation or intermittent detection of persistent infection. Without serologic evidence of prior infection, new detection is likely due to new acquisition or to intermittent detection of persisting infection.